Mitochondrial donation: A boon or curse for the treatment of incurable mitochondrial diseases - Nishtha Saxena; Nancy Taneja; Prakriti Shome; Shalini Mani (Wolters Kluwer Medknow Publications, 2018)
Mitochondria are present in all human cells and vary in number from a few tens to many thousands. As they generate the majority of a cell's energy supply which power every part of our body, and hence, their number varies in different cells as per the energy requirement of the cell. Mitochondria have their own separate DNA, which carries total 13 genes. All of these 13 genes are involved in energy production. For normal functioning of cells, the mitochondria need to be healthy. Unhealthy mitochondria can cause severe medical disorders known as mitochondrial disease. In case of mitochondrial disease, the most commonly affected organs are the heart, kidney, skeletal muscle, and brain. The diseases related to defects in these organs are quite prevalent in the society. Majority of these mitochondrial diseases are caused by genetic defects (mutations) in the mitochondrial DNA. Unlike nuclear genes, mitochondrial DNA is inherited only from our mother. Mothers can carry abnormal mitochondria and be at risk of passing on the serious disease to their children, even if they themselves show only mild or no symptoms. Due to the complex nature of these diseases, their diagnosis and therapy are very difficult. Hence, till now, only the different methods for management of these diseases are known. However, after understanding the complexity related to the cure of these diseases, alternative methods have been developed to minimize/stop the transfer of mitochondrial diseases from mother to offspring. This latest technique is called mitochondrial replacement or "donation." In the present review, we are discussing the methodological details and issues related to the technique of mitochondrial donation. Our study is also a step toward raising awareness about mitochondrial diseases and advocating for the legalization of mitochondrial donation, a revolutionary in vitro fertilization technique.